A 14-year literature survey on spine-related clinical research output by orthopedic surgeons from mainland China. Issue 34 (August 2018) - Si, Gao; Liu, Xiao; Xu, Nanfang; Yu, Miao; Liu, Xiaoguang
Abstract: Background: In recent years, China is increasingly playing an active role in various fields of biomedical research. Many bibliometric studies have provided valuable insights to different fields of clinical studies. However, similar evaluation on spine surgery-related clinical research is still limited. We herein aimed to examine the scientific publications by orthopedic spine surgeons from mainland China within a 14-year period. Methods: Articles were identified in PubMed using predetermined query terms. Descriptive statistics were calculated, and T tests, Chi-squared tests, and regression analysis were conducted on the number of publications, impact factors (IFs), citations, region of the study, and associated medical subject headings (MeSHs). Results: A total of 1498 articles were identified and the annual number of publications, citations, and IFs all increased exponentially. The average IF was significantly higher in 2007 to 2013 than 2000 to 2006. Most publications were from Shanghai and Beijing and the 5 most productive administrative regions generated 70% of all publications. Analysis of associated MeSHs suggested research topics became more heterogeneous over the study period. Conclusion: This was the first comprehensive evaluation on the clinical research output by orthopedic spine surgeons from mainland China. The annual number of publications and citations both increased significantly; however, research was highly concentrated in a handful of administrative regions.